2016
DOI: 10.1111/jfpp.12706
|View full text |Cite
|
Sign up to set email alerts
|

Shelf Life of Sliced Dry-Cured Ham Packaged Under Vacuum

Abstract: Dry-cured ham slices were stored under vacuum at 12 and 18C during 63 days. Organoleptic characteristics, color, pH, a w and microbial profile were evaluated throughout storage. Color parameters were not significantly affected by temperature and storage. pH was typical of dry-cured meat until 42 days of storage. Microbial profile was characterized by coagulase negative staphylococci and Pseudomonas spp. Total viable count showed a significant increase (P < 0.05) after 63 days when a spoilage level of 7 log was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 23 publications
3
0
1
Order By: Relevance
“…The decline in this parameter is in agreement with the findings of a previous study [ 41 ] on the effect of storage under vacuum conditions for 8 months on dry-cured ham quality. In contrast, another study [ 39 ] on the shelf life of sliced dry-cured ham packaged under vacuum with analysis performed in the same storage period as the present study reported an increase in pH during storage time. This increase has been associated with the release of amino acids and other basic compounds during the dry-maturation stage [ 42 ].…”
Section: Discussioncontrasting
confidence: 93%
See 1 more Smart Citation
“…The decline in this parameter is in agreement with the findings of a previous study [ 41 ] on the effect of storage under vacuum conditions for 8 months on dry-cured ham quality. In contrast, another study [ 39 ] on the shelf life of sliced dry-cured ham packaged under vacuum with analysis performed in the same storage period as the present study reported an increase in pH during storage time. This increase has been associated with the release of amino acids and other basic compounds during the dry-maturation stage [ 42 ].…”
Section: Discussioncontrasting
confidence: 93%
“…The pH values found in our study were similar to those reported in previous studies [ 39 , 40 ] in dry ham after a similar storage time. The decline in this parameter is in agreement with the findings of a previous study [ 41 ] on the effect of storage under vacuum conditions for 8 months on dry-cured ham quality.…”
Section: Discussionsupporting
confidence: 92%
“…At 4 °C, significant differences between measurements were observed on the 56 th day, whereas for samples stored at 20 °C, the first significant changes were observed on the 14 th day. The trend towards growing L * values during storage is similar to those detected by Piras et al [51] in dry-cured ham slices. Redness (a * value) is used as an indicator of colour stability in meat products [24].…”
Section: Resultssupporting
confidence: 89%
“…The slightly increase in the pH values of control group during the storage period is in agreement with the findings of [41] in stored sliced dry-cured ham for 63 days. It is also in accordance with [42] in dry-cured beef.…”
Section: Physicochemical Quality Phsupporting
confidence: 90%